2022
DOI: 10.1021/acs.jmedchem.2c01550
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TUL01101: A Novel Potent and Selective JAK1 Inhibitor for the Treatment of Rheumatoid Arthritis

Abstract: Janus kinase 1 (JAK1) is a potential target for the treatment of rheumatoid arthritis (RA). In this study, the introduction of a spiro ring with a difluoro-substituted cyclopropionamide resulted in the identification of TUL01101 (compound 36) based on a triazolo[1,5-a]pyridine core of filgotinib. It showed excellent potency on JAK1 with an IC50 value of 3 nM and exhibited more than 12-fold selectivity for JAK2 and TYK2. Whole blood assay also demonstrated the high activity and selectivity (37-fold for JAK2). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
(169 reference statements)
0
12
0
Order By: Relevance
“…). 17e was synthesized in 49% yield according to the same procedure as 16a using the intermediate 12 (0.25 mmol) and 3-cyanobenzaldehyde (0.5 mmol); 1 H NMR (400 MHz, DMSO-d 6 ) δ 11.52 (s, 1H), 9.63 (d, J = 8.7 Hz, 1H), 8.32 (s, 1H), 8.24 (d, J = 4.5 Hz, 1H), 7.78−7.72 (m, 2H), 7.69 (d, J = 7.9 Hz, 1H), 7.57 (t, J = 7.7 Hz, 1H), 7.17 (dd, J = 3.2, 2.2 Hz, 1H), 6.51 (d, J = 2.4 Hz, 1H), 4.86 (d, J = 49.4 Hz, 1H), 4.30−4.14 (m, 1H), 3.63 (s, 2H), 3.06 (t, J = 9.3 Hz, 1H), 2.81−2.77 (m, 1H), 2.75 (d, J = 4.4 Hz, 3H), 2.51 (dd, J = 35.7, 12.9 Hz, 1H), 2.34 (t, J = 10.6 Hz, 1H), 1.90 (d, J = 9.7 Hz, 1H), 1.80 (q, J = 10.7 Hz, 1H); 13 1-Benzyl-2,2-dimethylpiperidin-4-amine (30). To a solution of intermediate 27 (1 equiv) in methanol (10 mL) were added ammonium acetate (10 equiv) and 4 Å molecular sieves and stirred for 1 h for the conversion of carbonyl groups of intermediate 27 to amine.…”
Section: -((Cis-1-(3-cyanobenzyl)-3-fluoropiperidin-4-yl)amino)-nmeth...mentioning
confidence: 99%
See 3 more Smart Citations
“…). 17e was synthesized in 49% yield according to the same procedure as 16a using the intermediate 12 (0.25 mmol) and 3-cyanobenzaldehyde (0.5 mmol); 1 H NMR (400 MHz, DMSO-d 6 ) δ 11.52 (s, 1H), 9.63 (d, J = 8.7 Hz, 1H), 8.32 (s, 1H), 8.24 (d, J = 4.5 Hz, 1H), 7.78−7.72 (m, 2H), 7.69 (d, J = 7.9 Hz, 1H), 7.57 (t, J = 7.7 Hz, 1H), 7.17 (dd, J = 3.2, 2.2 Hz, 1H), 6.51 (d, J = 2.4 Hz, 1H), 4.86 (d, J = 49.4 Hz, 1H), 4.30−4.14 (m, 1H), 3.63 (s, 2H), 3.06 (t, J = 9.3 Hz, 1H), 2.81−2.77 (m, 1H), 2.75 (d, J = 4.4 Hz, 3H), 2.51 (dd, J = 35.7, 12.9 Hz, 1H), 2.34 (t, J = 10.6 Hz, 1H), 1.90 (d, J = 9.7 Hz, 1H), 1.80 (q, J = 10.7 Hz, 1H); 13 1-Benzyl-2,2-dimethylpiperidin-4-amine (30). To a solution of intermediate 27 (1 equiv) in methanol (10 mL) were added ammonium acetate (10 equiv) and 4 Å molecular sieves and stirred for 1 h for the conversion of carbonyl groups of intermediate 27 to amine.…”
Section: -((Cis-1-(3-cyanobenzyl)-3-fluoropiperidin-4-yl)amino)-nmeth...mentioning
confidence: 99%
“…Nonetheless, it is currently postulated that the pursuit of JAK-selective inhibitors tailored to target specific signals associated with each JAK rather than broadly inhibiting all cytokine signaling holds a significant advantage for achieving toxicity control . For this reason, researchers are developing selective inhibitors , for each JAK to achieve more targeted and effective treatments with fewer side effects. Although further research is necessary to draw definitive conclusions regarding their long-term safety profiles, initial studies have shown that selective inhibitors are generally less toxic than broad-spectrum inhibitors …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,4-Triazole has been widely employed as a key structure of numerous bioactive small molecules (Figure ). Indeed, it is a substructure of many therapeutic agents being developed as well as clinically used medicines such as triazolam, trapidil, and sitagliptin. Despite its prevalence in functional chemicals, 1,2,4-triazole-fused ring systems have been relatively less explored .…”
Section: Introductionmentioning
confidence: 99%